The Design Analysis of Resistance to Brittle Crushing of WWER-1000 Reactor Head. (March 2019) - Ovsenev, A E; Pimenov, N; Bibik, I S
Abstract: The basic equipment of reactor plant WWER-1000 is operated under the severe conditions. The reactor head is no exception because this construction is subjected to severe dynamic and temperature influence which causes a degradation of its material properties during the operation. This construction is made of rugged material which is capable of sustaining all impacts occurring at the planned operation lifetime, but some head sections are more subjected to a brittle crushing.